Final girl vs. serial Killer: a psychoanalytical analysis of female victim-heroes in serial killer films - Özgenalp, Nur (İstanbul Bilgi Üniversitesi, 2006)
The aim of this study is to understand the role of female protagonists in serial killer movies.This dissertation analyzes In the Cut (Campion, 2003), Taking Lives (Caruso, 2004) and MaryReilly (Frears, 1996) as an example of films which have a specific common quality. Startingwith The Silence of the Lambs (Demme, 1991), there has been a substantial increase in thenumber of films that tell the story of male serial killers who are investigated by females. Filmswith same identical properties; such as Twisted (Kaufman, 2004), Copycat (Amiel, 1999),1996), Kiss the Girls (Fleder, 1997), Murder by Numbers (Schroeder, 2002), Tesis(Amenábar, 1996) and The Bone Collector (Noyce, 1999); followed The Silence of the Lambs.All These films hold the essential properties of serial killer films that have femaleprotagonists who have a sexual relationship with the killer and, at the end, overcome thekiller. This female is similar to Final Girls whom Clover has theorized while examiningslasher films. Therefore this dissertation first analyzes the basic elements of horror films, andthen it examines a new type of serial killer films with psychoanalytic theories and compares itto Clover’s slasher films. Starting with general aspects of horror films, it focuses on slasherfilms - a subgenre of horror films. Afterwards, it goes on to compare In the Cut (Campion,2003), Taking Lives (Caruso, 2004) and Mary Reilly (Frears, 1996) with slasher films.Although these films differ in many aspects, they still share common qualities. This studyattempts to analyze these common qualities that can be traced back to slasher films. In theend, having discussed how slasher films have evolved into serial killer films with femalevictim-heroes, this thesis continues discussing the role of the female victim-heropsychoanalytically by studying Clover’s theories of identification and Final Girls

Bu çalısmanın amacı seri katil filmlerindeki kadın kahramanların rolünü anlamaktır. Bu tezbelli ortak özellikler tasıyan In the Cut (Campion, 2003), Taking Lives (Caruso, 2004) veMary Reilly (Frears, 1996) adlı filmleri analiz ediyor. The Silence of the Lambs (Demme,1991) filmiyle birlikte seri katilleri arastıran kadın kahramanların oldugu filmlerin sayısındabir yükselme oldu. Aynı temel özellikleri tasıyan Twisted (Kaufman, 2004), Copycat (Amiel,1999), Kiss the Girls (Fleder, 1997), Murder by Numbers (Schroeder, 2002), Tesis(Amenábar, 1996) ve The Bone Collector (Noyce, 1999) The Silence of the Lambs’ı takip etti.Bütün bu filmler, seri katille cinsel iliskiye giren ve filmin sonunda onları alt eden kadınkahramanların oldugu seri katil filmlerinin temel özelliklerini tasıyorlar. Bu kadın tipi,Clover’ın slasher filmleri incelerken öne sürdügü Final Girl tipine benzemektedir. Bu sebeple,bu tez, öncelikle, korku filmlerinin temel özelliklerini inceliyor, ardından da yeni bir seri katilfilmleri türünü psikanalitik teorilerle analiz ediyor ve bu filmleri Clover’ın slasher filmleriylekarsılastırıyor. Korku filmlerinin genel özelliklerini tanımlamakla basladıktan sonra korkujanrının bir alt janrı olan slasher filmlere odaklanıyor. Ardından da In the Cut (Campion,2003), Taking Lives (Caruso, 2004) ve Mary Reilly (Frears, 1996) filmlerini slasher filmlerlekarsılastırıyor. Bu filmler bazı karakteristikleri açısından farklı olsalar da ortak özellikleri agırbasıyor. Bu çalısma bu ortak özellikleri analiz ediyor ve onların kökenini slasher filmleredayandırıyor. Bu tez kadın kurban-kahramanların yer aldıgı seri katil filmlerinin slasherfilmlerinin yeniden biçimlenmis halleri oldugunu kanıtlamaya çalıstıktan sonra, bufilmlerdeki kadın kurban-kahramanların rollerini psikanalatik açıdan tartısıyor. Bunun için deClover’ın “identification” ve Final Girl teorilerini inceliyor.
Final girl seri katile karşı: seri katil filmlerindeki kadın kurban-kahramanlar üzerine psikanalitik bir inceleme